Digitalizing health services by implementing a personal electronic health record in Germany: qualitative analysis of fundamental prerequisites from the perspective of selected experts - Pohlmann, Sabrina; Weis, Aline; Ose, Dominik; Winkler, Eva C.; Brandner, Antje; Poß-Doering, Regina; Szecsenyi, Joachim; Wensing, Michel (Journal of medical internet research, 2020)
Background: The implementation of a personal electronic health record (PHR) is a central objective of digitalization policies in the German health care system. Corresponding legislation was passed with the 2015 Act for Secure Digital Communication and Applications in the Health Sector (eHealth Act). However, compared with other European countries, Germany still lags behind concerning the implementation of a PHR. - Objective: In order to explore potential barriers and facilitators for the adoption of a PHR in routine health care in Germany, this paper aims to identify policies, structures, and practices of the German health care system that influence the uptake and use of a PHR. - Methods: A total of 33 semistructured interviews were conducted with a purposive sample of experts: 23 interviews with different health care professionals and 10 interviews with key actors of the German health care system who were telematics, eHealth, and information technology experts (eHealth experts). The interviews were transcribed verbatim and subjected to a content analysis. - Results: From the expert perspective, a PHR was basically considered desirable and unavoidable. At the same time, a number of challenges for implementation in Germany have been outlined. Three crucial themes emerged: (1) documentation standards: prevailing processes of the analog bureaucratic paper world, (2) interoperability: the plurality of actors and electronic systems, and (3) political structure: the lack of clear political regulations and political incentive structures. - Conclusions: With regard to the implementation of a PHR, an important precondition of a successful digitalization will be the precedent reform of the system to be digitized. Whether the recently passed Act for Faster Appointments and Better Care will be a step in the right direction remains to be seen. - [J Med Internet Res 2020;22(1):e15102]
Gesehen am 06.05.2020